Toleransi Umat Beragama (Antar pemeluk Seagama) dalam Tinjauan Tafsir Izwaji (Tolerance of Religious People - Between Adherents of One Religion - in The Review of Tafzir Izwaji) - Musthofa Musthofa (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2019)
The tolerance of people in one religion is an attitude or action by respecting each other and respecting the practices based on truth in accordance with their understanding within certain limits. The tolerance of internal religious communities in the Izwaji Interpretation Review can be done by: (1) giving knowledge, including: not forcing other denominations, not insulting followers of other groups, not disturbing the rituals or rituals of other followers, not slandering fellow believers, please help between group followers, and (2) friendship, including: giving and receiving greetings when met or separated, responding to invitations by religious groups, giving advice when asked and giving advice, responding to prayers when religious friends sneeze in praise of God, visiting when sick (tomorrow) among religious converts , and accompanying the body when a fellow religion dies.